A comparison of PV resource modeling for sizing microgrid components. (December 2020) - Newman, Sarah; Shiozawa, Kaymie; Follum, Jim; Barrett, Emily; Douville, Travis; Hardy, Trevor; Solana, Amy
Abstract: Microgrid systems are being deployed with increased frequency to meet critical building loads during unplanned power outages. Determining the appropriate type and size of components that make up a microgrid can greatly affect its ability to meet this need. This paper presents a new tool to appropriately size PV, battery, and generator capacities to meet all site loads, given a resilience goal. It uses a statistical model to simulate microgrid behavior under a large range of solar resource conditions, providing resilience planners with confidence that critical loads will be met even under extreme weather conditions. We compare this model with one that uses typical weather data for sizing microgrids, and quantify the resilience effects of using these different methods. Our method produces more conservative generator capacities and fuel requirements in an outage, predicting up to 30% more fuel required in the most extreme case. Microgrid systems that are designed using more conservative estimates are more likely to continue to serve load during emergency outages under a large range of conditions. Highlights: Typical weather data is insufficient for modeling emergency microgrid operation . The MCOR tool simulates solar resources under varied conditions. This model predicts more conservative microgrid resources than other methods. Site resilience requires modeling microgrid operation during extreme conditions .